ANALISIS PENGARUH UKURAN PERUSAHAAN DAN MEKANISME CORPORATE GOVERNANCE TERHADAP EARNING MANAGEMENT - Siregar, Nolita Yeni (JAK (Jurnal Akuntansi) : Kajian Ilmiah Akuntansi, 2017)
This research is aimed to get an empirical evidence about the influence of the size of the company, and the corporate governance mechanism on the earnings management. Firm size was measured by using the natural logarithm of the total sales of the company and corporate governance mechanisms were measured using five variables (institutional ownership, managerial ownership, the size of the board of directors, independent board and audit committee). Earnings management is measured by discretionary accruals using  Modified Jones Model. The population in this study is 132 companies listed in the Indonesia Stock Exchange in 2012-2014. The research data was obtained from the manufacturing company's financial statements in the 2012-2014 period. Based on the purposive sampling method, the sample was obtained as 30 companies. The hypothesis in this study were tested using multiple regression analysis. The analysis showes that the ownership managerial variable has a significant influence on earnings management, the size of the board of directors and audit committee. Where as, the company variable size, institutional ownership and the independent board do not significantly affect the earnings management.  Key words : Size of the company, corporate governance, earnings managemen